Comparison of metabolic pathways in insect symbiotic bacteria - Schürz, Robin (Jihočeská univerzita, 2022)
Genomes of lice endosymbionts, Legionella from two different host species (Polyplax serrata and Polyplax spinulosa), were compared in their metabolic pathways. Preserved genes were annotated, mapped out for comparison and checked for their functionality. The annotated genes also were assessed for their Ka/Ks values and the COG categories they were included in.
Comparison of metabolic pathways in insect symbiotic bacteria
Keywords: insect symbionts; Legionella polyplacis; Polyplax serrata; Polyplax spinulosa; endosymbiosis; lice; blood sucking lice; Ka/Ks value; COG category; metabolism; metabolic pathway; GC content; insect symbionts; Legionella polyplacis; Polyplax serrata; Polyplax spinulosa; endosymbiosis; lice; blood sucking lice; Ka/Ks value; COG category; metabolism; metabolic pathway; GC content